Effect of Exercise on Glycemic Status of Patients Suffering from type 2 Diabetes Mellitus (Journal of Dhaka National Medical College & Hospital, 2013)
Background: The number of people with diabetes is now considered to have reached epidemic proportions. Globally the incidence rate of type 1 and particularly type 2 diabetes are increasing in all societies. Type 2 diabetes is highly prevalent in elderly and is now emerging in childhood and accounts for more than 95% of all diabetes. Due to the rising tide of type 2 diabetes, it is a major international challenge for optimal intervention and prevention strategies. Objective: To see the effectiveness of exercise in type to diabetic patient . Materials and Methods: The study was carried out in the department of physiology of Mymensingh Medical College from July 2007 to June 2008. To assess glycemic status we estimate pre and post exercise blood glucose and glycated hemoglobin level of 101 study group whose age ranged from 38-70 years. Result:  During the study time in this group of population pre and post exercise blood glucose level was respectively 9.18 mmoI/L and 8.05 mmoI/L, P vale ˂ 0.001,indicate the significance of exercise. Regular exercise for a period of 30 to 40 minutes in the form of walking seems to improve the glycemic status in type 2 diabetes mellitus. Conclusion: It can be concluded that regular  exercise for a period of 30 to 40 munites in the form of walking seems to control blood glucose level within normal range in type 2 diabetes mellitus. So, health care professionals  must address exercise in those patients as  a part of treatment.J. Dhaka National Med. Coll. Hos. 2013;19 (01): 6-10